Decrease of psychomotor performance in subjects with latent 'asymptomatic' toxoplasmosis - Havlícek, J; Gasová, Z G; Smith, A P; Zvára, K; Flegr, J (Parasitology, 2001)
Toxoplasma gondii is known to induce specific behavioural changes in its intermediate hosts. This is usually considered to be an evolutionary adaptation aimed to increase the probability of transmission of the parasite into its definitive host, the cat, by predation. In rodents an increase of reaction time as well as many other specific behavioural patterns have been observed. Here we report the results of our double blind study showing the significantly longer reaction times of 60 subjects with latent toxoplasmosis in comparison with those of 56 controls. Moreover, the existence of a positive correlation between length of infection and mean reaction time suggested that slow and cumulative effects of latent toxoplasmosis rather than a one-step (and possibly transient) effect of acute toxoplasmosis disease are responsible for the decrease of psychomotor performance of infected subjects. To our knowledge, this is the first study confirming the existence of such parasite-induced changes in human behaviour that could be considered in evolutionary history of the human species as adaptive from the point of view of parasite transmission.
Keywords: Animals; Reaction Time; toxoplazmóza; lidé; psychomotorický výkon; dvojitá slepá metoda; zvířata; Double-Blind Method; Psychomotor Performance; Toxoplasmosis; Toxoplasma; reakční čas; Humans